Analysis of Service Satisfaction and Complaint Handling Efforts of District Road Users in the Serang District Government - Alynudin, Suhud (Jurnal Manajemen Pelayanan Publik, 2025)
Highways are public services provided by the government, as an important infrastructure for community mobility. This study aims to assess the level of public satisfaction with road services and identify complaints submitted by road users. This study used a quantitative approach with 196 respondents, using the Lemeshow formula (population unknown), and using purposive sampling techniques. Data was collected through a closed questionnaire and data was analyzed using the following methods: Importance Performance Analysis (IPA), Customer Satisfaction Index (CSI), and Complaint and Suggestion Analysis. The results of the IPA are that of the 33 statements, 2 items are in Quadrant I, 9 items are in Quadrant II, 15 items are in Quadrant III, and 7 items are in Quadrant IV. The CSI score was calculated at 69.00%, showing that road users in Serang Regency were quite satisfied. In addition, the analysis of complaints and suggestions from users, including the repair of potholes, damaged road shoulders and bridges, installation and maintenance of street lighting, procurement of drainage systems and culverts. These findings are important inputs in the preparation of work programs and budgeting in the road infrastructure sector and formulating policies based on the real needs of road users.